2009
DOI: 10.1590/s0102-67202009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Apendicite aguda: análise institucional no manejo peri-operatório

Abstract: A apendicite aguda é a causa mais comum de abdômen agudo na criança, no adolescente e no adulto jovem com um pico de incidência na 2° e 3° décadas de vida. O risco de um indivíduo apresenta-la durante a vida inteira é de 7% 7,25,26 . Sua incidência reduziu-se nas últimas décadas e as razões desse declínio ainda não estão esclarecidas, tendo sido atribuídas às mudanças nos hábitos dietéticos e na flora intestinal, melhora da nutrição, maior ingestão de vitaminas e outros 16 .A obstrução da luz apendicular é o p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
12
0
4
Order By: Relevance
“…Acute appendicitis is a common diagnosis in the emergency unities 4,6,13,15 . Most of the cases occur in younger populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute appendicitis is a common diagnosis in the emergency unities 4,6,13,15 . Most of the cases occur in younger populations.…”
Section: Discussionmentioning
confidence: 99%
“…A cute appendicitis is the most common surgical disease presented in patients at emergency unities 4,6,11,12,13,15 . Defined as the presence of transmural infection of the cecal appendix, it is an infection that can be presented in initial stage as edematous or suppurative appendicitis or late with gangrene or perforation 5,18 .…”
Section: Introdutionmentioning
confidence: 99%
“…Is suggested that between 6.7% and 8.6% of the people of the Western world submit appendicitis at some point in their lives 1,8 . Although thousands of appendectomies are performed annually worldwide, the treatment of appendicular stump has not been uniform.…”
Section: Abcddv/753mentioning
confidence: 99%
“…The choice of the technique for management of the stump depends mostly in the surgeons preference or due to the protocol adoption by the hospital 8 , 13 , 17 , 23 . When the length of stay in the hospital is evaluated, the importance of surgical technique is surpassed by other determinant factors, such as pre-operative duration of illness, response to antibiotics and the presence of comorbities.…”
Section: Introductionmentioning
confidence: 99%